Manajemen Pertukaran Gas pada Pasien Post CARDS (COVID-19 Acute Respiratory Distress Syndrome) yang Terpasang Ventilasi Mekanik - Ida Amalia; Riri Maria; Dewi Irawaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the effectiveness of prone intervention in cases of post-CARDS/COVID-19 Acute Respiratory Distress Syndrome who are mechanically ventilated. This type of research is research with a case study approach. The results showed that after the intervention was given in the prone position in patients with post CARDS/Covid-19 Acute Respiratory Distress Syndrome who had mechanical ventilation installed, there was an increase in oxygen saturation values and also to prevent secondary injuries that could worsen the condition of the lungs and other organs. In conclusion, prone position performed as early as possible will be better and provide a significant improvement effect on the respiratory system. Keywords: ARDS, CARDS, COVID-19, Gas Exchange Disorders, Prone